VERBA NASALISASI N- (ATAU NG-?) DALAM BAHASA BALI - W. A. Sindhu Gitananda (Pascasarjana Universitas Hindu Indonesia, 2017)
The Balinese has uniqueness concerning its verbs, especially those undergone the process of nasal- ization (using prefix N- (Ng-)). By this phenomenon, it is really interesting to analyze the variation of the nasalized verbs morphophonemically and their syntactic function in the Balinese sentences. Re- garding these concerns, the descriptive-qualitative method was applied. Therefore, it can be concluded that the nasalized verbs with N- (Ng-) are varied morphophonemically (having complementary distri- bution) through the allomorphs as /n-/, /m-/, /ng-/, and /ny-/. The distributions depend on the initi- ating phoneme of the stems that undergo the process of affixation. Then, the function of the nasalized verbs with N- (or Ng-) is as the nucleus of the cores or predicates to form active sentences that have maximally two arguments.